A Rare Case Report of Invasive Ocular Surface Squamous Neoplasm of Conjunctiva - Patil, Noopur Subhash; Kanthikar, Shivraj N; Chege, Prashant B; Kulkarni, Sheela N (Annals of Pathology and Laboratory Medicine, 2020)
Ocular surface neoplasm(OSSN) represent a rare but broad spectrum of disease, including mild dysplasia on one end of the spectrum and invasive Squamous cell carcinoma(SCC) on the other. Thus, the diagnosis completely depends on histopathological examination of the lesion. The incidence of ocular surface neoplasia is strongly associated with factors like solar ultraviolet radiation, HIV and human papilloma virus(HPV) infections. Most lesions occur at the limbus within the interpalpebral fissure particularly the nasal side. Their importance lies in the fact that they mimic benign lesions like pterygium or even chronic conjunctivitis and thus can be misinterpreted and inadequately treated. Red eye and ocular irritation are the most common presenting symptoms. No tumor related deaths or metastasis are generally seen. Surgery with intra-operative control of surgical margins and adjunctive chemotherapy, immunotherapy and cryotherapy result in good tumor control rates, with promising results in aggressive, recurrent and large tumors.